Pengaruh Struktur Modal, Likuiditas Dan Ukuran Perusahaan Terhadap Profitabilitas Pada Sub Sektor Food And Beverage Di Bursa Efek Indonesia Periode 2020 - 2022 - Lidia Wulandari; Indria Widyastuti (Jurnal Akuntansi Bisnis dan Ekonomi (JABE), 2023)
This research was conducted to examine the effect of the variables capital structure, liquidity and company size on profitability partially in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. In addition, to test the feasibility of the variable influence regression model; capital structure, liquidity, and company size on profitability simultaneously in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The population in this study is 47 companies that have been and are still listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique used ispurposive sampling and obtained a sample of 17 companies. The data analysis technique used is to use multiple linear regression tests. The results showed that the capital structure partially affects profitability. Other variables in this study, namely liquidity partially has no significant effect on profitability, and company size partially has no effect on profitability. Simultaneously, capital structure, liquidity and company size have no effect on profitability. The predictive ability of the three variables on profitability is 9.90% as indicated by the magnitude adjusted R squre of 0.099 while the remaining 90.1% is influenced by other factors not included in the research model.